Augmented Reality Marketing: A Technology-Enabled Approach to Situated Customer Experience. Issue 4 (November 2020) - Chylinski, Mathew; Heller, Jonas; Hilken, Tim; Keeling, Debbie Isobel; Mahr, Dominik; de Ruyter, Ko
Recent advances in Augmented Reality (AR) technologies have led to a growing interest in their application for marketing strategy and practice – what we term Augmented Reality Marketing (ARM). However, despite emerging publications on the subject, managers and academics struggle to articulate how ARM delivers experiences that are valuable to customers in a way that is different from other marketing approaches. In this article, we review the emerging literature, and define ARM as a customer-facing interface for the application of digital marketing technologies in physical settings. Rooted in a class of 'situated cognition' theories from social psychology, we identify a unique set of digital affordances which ARM offers beyond extant marketing approaches in traditional media. By drawing on the key conceptual building blocks of situated cognition theory, we develop a framework of ARM experiences to synthesize current research and applications, and to suggest directions for future research.